Post‐traumatic missing talus: Staged allograft interposition and fusion. Should we fuse the "talo‐navicular" joint?. Issue 9 (14th September 2022) - Kitridis, Dimitrios; Lampridis, Vasileios; Rigkos, Dimitrios; Savvidis, Ioannis; Georgiannos, Dimitrios; Bisbinas, Ilias
Abstract: Complete talar dislocation—extrusion is an uncommon sequela of high‐energy trauma. When the talus is unavailable for reimplantation, a staged treatment plan with the use (a) of an antibiotic cement spacer, followed by (b) tibiotalocalcaneal fusion with bone allograft interposition, may ensure a good clinical outcome. Abstract : Complete talar dislocation—extrusion is an uncommon sequela of high‐energy trauma. When the talus is unavailable for reimplantation, a staged treatment plan with the use (a) of an antibiotic cement spacer, followed by (b) tibiotalocalcaneal fusion with bone allograft interposition, may ensure a good clinical outcome.